DYSTOCIA DUE TO SCHISTOSOMUS REFLEXUS IN A MURRAH BUFFALO - KUMAR, SHARAD; KUMAR, SUDHIR; SHARMA, UTSAV; KUSHWAHA, R B; PANDEY, A K (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia in a Murrah she buffalo due to Schistosomus reflexus is reported and discussed.